Can Tirofiban Improve the Outcome of Patients With Acute Ischemic Stroke: A Propensity Score Matching Analysis - Cai, Lingxin; Yu, Xiaobo; Yu, Jun; Xu, Jing; Xu, Liang; Ling, Chenhan; Lou, Min; Yu, Cheng; Qian, Cong (Frontiers in Neurology, 2021)
Objective: To evaluate the efficacy and safety of tirofiban for patients with acute ischemic stroke (AIS), especially posterior circulation stroke (PCS). Methods: We enrolled consecutive patients with AIS who suffered large artery occlusion (LAO) and underwent mechanical thrombectomy (MT) between January 2016 and May 2020. Patients were divided into two groups according to whether tirofiban was used during MT. The primary efficacy outcome was a favorable functional outcome, defined as a modified Rankin Scale (mRS) score of 0–2 at 3 months. The safety outcomes were the rate of mortality at 3 months and the presence of intracranial hemorrhage (ICH) and symptomatic intracranial hemorrhage (sICH). Cohorts were balanced using 1:1 propensity score matching (PSM). Subgroup analysis was further performed to compare the efficacy and safety of tirofiban between the anterior circulation stroke (ACS) and PCS groups. Results: A total of 292 patients were eligible for this study and divided into the tirofiban group (n = 51) and the no-tirofiban group (n = 241). In the propensity-score-matched cohort, the tirofiban group had a higher rate of favorable outcomes than the no-tirofiban group (49.0 vs. 25.5%, p = 0.014), and the mortality at 3 months showed a greater downward trend in the tirofiban group than the no-tirofiban group (15.6 vs. 33.3% p = 0.064). The risk of sICH and ICH was the same between the tirofiban and control groups (17.6 vs. 27.4% p = 0.236, 31.3 vs. 45.1% p = 0.154, respectively). Tirofiban use was predictive of favorable outcomes [adjusted odds ratio (aOR) = 2.87, 95% confidence interval (CI) 1.52–6.44, p = 0.043] after multiple logistic regression analysis. Subgroup analysis revealed that tirofiban use was significantly associated with favorable outcomes in ACS (aOR = 3.66, 95% CI 1.24–5.22, p = 0.019) but not in PCS (aOR = 1.12, 95% CI 0.47–7.52, p = 0.570). Conclusion: We demonstrated that tirofiban may be associated with improving favorable outcome for the AIS patients who underwent MT, without increasing ICH or sICH. Furthermore, our results indicated that for PCS patients tirofiban may not be associated with favorable outcome, and more comprehensive randomized controlled trials are needed to confirm this finding.